The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1590/abd1806-4841.20153339
|View full text |Cite
|
Sign up to set email alerts
|

Granuloma faciale: a good therapeutic response with the use of topical tacrolimus

Abstract: Granuloma faciale is a rare dermatosis of chronic course, benign, usually asymptomatic, first described in 1945 by Wingley. It is characterized by the appearance of well-defined, single or multiple papules, plaques and nodules, predominantly located in sun-exposed areas, especially the face. In this work we report the case of a female patient, 58 years old, evolving for ten years with multiple erythematous-brownish and asymptomatic papules on the face, whose histological examination confirmed the diagnosis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The specificity of the disease in terms of its refraction to treatment constitutes a challenge for doctors and causes a psychological problem for the patient. However, more recent studies have shown good results after four months with topical tacrolimus 0.1% [10]. Meanwhile, other studies have shown good and promising results with intralesional rituximab [11].…”
Section: Discussionmentioning
confidence: 99%
“…The specificity of the disease in terms of its refraction to treatment constitutes a challenge for doctors and causes a psychological problem for the patient. However, more recent studies have shown good results after four months with topical tacrolimus 0.1% [10]. Meanwhile, other studies have shown good and promising results with intralesional rituximab [11].…”
Section: Discussionmentioning
confidence: 99%
“…Possible adverse effects of this treatment have been described, such as residual hyperchromia and telangiectasias [8].…”
Section: Discussionmentioning
confidence: 99%